Challenges Associated with the Effective Management of HIV Infection in a Low Income Setting in Sub Saharan Africa: Case Study of Nigeria - Erhabor, Osaro; Ejele, Oseikhuemen Adebayo; Nwauche, Chijioke Adonye; Akani, Chris; Cosmos, Eyindah; Allagoa, Dennis; A.D., Edward Alikor; C., Ojule Aaron; Opurum, Hamilton; Obunge, Orikomaba; Babatunde, Seye; Frank-Peterside, Nnenna; et al. (IntechOpen, 2011)
None